The hand book of Muslim family laws - Bangladesh; Chowdhury, Obaidul Huq.; Dhaka Law Reports (Firm) (Dhaka : Dhaka Law Reports, 2005)
Contains upto date amendments of the acts, ordinance, rules including case laws.
Includes index.
Includes passages in Bengali.
Keywords: Domestic relations (Islamic law) -- Bangladesh